2019
DOI: 10.1111/jphp.13102
|View full text |Cite
|
Sign up to set email alerts
|

Development, physico-chemical characterization and in-vitro studies of hydrogels containing rosmarinic acid-loaded nanoemulsion for topical application

Abstract: Objectives Natural sources with antioxidant activity, such as rosmarinic acid (RA), have been considered as an interesting approach for the development of new anti‐ageing skin products. In this context, this study aimed to develop hydrogels containing RA‐loaded nanoemulsions and evaluate the effect of the addition of Tween® 80 (a nonionic cosurfactant) in formulations intended to be used for topical application. Methods Physico‐chemical characterization, in‐vitro release and skin retention/permeation from hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…They presented promising effects on in vitro cell proliferation and keratinocyte migration, combined with an indication for the absence of cytotoxicity and non-irritating potential [13]. For topical application, the low viscosity of nanoemulsions is a concern, and the design of a semisolid formulation is an important consideration [15][16][17]. The present study is the first to describe the development of semisolid formulations containing A. satureioides extract for in vivo topical application in wound healing and to use nanotechnology-based products to improve flavonoid skin retention/permeation, because the small droplet sizes can improve active penetration of lipophilic molecules through the skin, increasing their topical effect.…”
Section: Introductionmentioning
confidence: 99%
“…They presented promising effects on in vitro cell proliferation and keratinocyte migration, combined with an indication for the absence of cytotoxicity and non-irritating potential [13]. For topical application, the low viscosity of nanoemulsions is a concern, and the design of a semisolid formulation is an important consideration [15][16][17]. The present study is the first to describe the development of semisolid formulations containing A. satureioides extract for in vivo topical application in wound healing and to use nanotechnology-based products to improve flavonoid skin retention/permeation, because the small droplet sizes can improve active penetration of lipophilic molecules through the skin, increasing their topical effect.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, drug immobilization in a polymer matrix should be considered in the context of controlled release at target sites. Various in vivo and in vitro drug application techniques have been developed with various therapeutic properties [12,[22][23][24], including antifungal [25][26][27], antibacterial [28][29][30][31][32], antitumor [33][34][35][36], anti-inflammatory [37,38], immunomodulatory [39][40][41], anti-glycemic [42], antioxidant [32,37,43], tissue repair and regeneration [14,16,44].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogel of RA-loaded nanoemulsions were prepared by using 2.5% w/v of egg-lecithin, 6% w/v of medium chain triglyceride (MCT), water 1% w/v of Tween ® 80 (polysorbate 80) a nonionic surfactant and dispersed in hydroxyethyl cellulose. In-vitro RA release studies performed in a Franz type diffusion cell showed that about 60% of RA is released in 8 h and skin retention studies evidenced that 0.65 ± 0.08 µg/cm 2 of RA were retained in total skin [127].…”
Section: Bionanosystems Based On Organic Carriersmentioning
confidence: 97%